Все было так, как было: избранные произведения / Леонид Смелков ; [предисловие автора] - Смелков Леонид Федорович (2016)
Экземпляры: ЦБ (20241111) / Инвентарный номер: 61669 / Цена: 100.00 / Сис.шифр: К 84 / Авт.знак: С 50 / ГРНТИ: 17.82.10 / ББК: 84(2=664.1)6-5